Peran Kecerdasan Emosional Dalam Meningkatkan Motivasi Dan Dinamika Kelompok di Tempat Kerja - Fadilul Rahman; Nasywa Faiza Khairani; Khairunnisa Luqyana; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Emotional intelligence (EI) plays a critical role in enhancing individual motivation and team dynamics in the workplace. This study examines the impact of EI on employees’ ability to recognize, manage, and adapt their emotions, as well as understand others’ emotions, to support team and organizational performance. An analytical literature review approach was employed, integrating recent theories and research findings on EI dimensions, including self-awareness, self-regulation, empathy, self-motivation, and social skills. The results indicate that EI not only improves individual effectiveness but also strengthens communication, collaboration, and team cohesion, while fostering employees’ intrinsic motivation. Practical implications highlight the importance of emotional competence-based training programs to enhance motivation, build team collaboration, and improve overall organizational performance. EI is a strategic asset for developing a productive and adaptive work culture.